Мodern Approaches to the Treatment and Prevention of Recurrent of Ophthalmic Herpes. Review - G. Ch. Zaynutdinova (Oftalʹmologiâ)
The review focuses on modern treatment aspects and prevention of ophthalmic herpes.The generalized experience of the clinical nucleoside administration, the basic antiviral drugs in the treatment of this pathology, is presented in detail. Information about indications, side effects and various schemes for their systemic and local application is provided. Questions on the duration of nucleoside administration in various clinical forms of eye herpes are considered. A meta-analysis of the comparative therapeutic nucleoside efficacy based on the results of more than 100 placebo-controlled randomized trials is presented. Special attention is paid to the rare but severe eye pathology, the acute retinal necrosis. Also data on the indications and contraindications of corticosteroids and on the current view of immunotherapy of ophthalmic herpes is presented. The question of the modern approach to the disease prevention recurrences is considered in detail, particularly, the results of the nucleoside administration have a high level of evidence, and, herpetic vaccines in the rehabilitation of patients with herpes infection are not widely used due to the lack of reliable methods for evaluating the efficacy. The information on the search for new effective drugs that have a targeted effect on certain patient cell receptors that can inhibit the penetration and spread of the herpes virus that can cause a controlled immune response is provided. Expanding the arsenal of effective and safe antiviral therapy will definitely optimize the treatment of ophthalmic herpes and prevent the occurrence of its recurrence and severe outcomes.